(untitled) (Al-Qamar, 2024)
The entire crux of Islam and the complete treasure of Shariah rest upon the life of the Messenger of Allah (PBUH). His sayings, actions, morals and habits are not hidden from anyone, and they serve as the source of guidance for all Muslims. The Companions of the Prophet (PBUH) preserved every single word of the Prophet’s (PBUH) life, in such a way that no aspect remained hidden – whether in private or public, during travel or residence, from personal affairs to global political matters. They used to mention the hadiths of the Prophet (PBUH) and preserved them from their chests to the scriptures. After them, the successors of them continued this process, until after the second century Hijri, the formal compilations of hadiths began. The books of hadiths were compiled systematically providing the comprehensive portrait of the Prophet’s life and complete picture of Islam. Therefore, the denial of the hadith based on the compilation of the hadith, when evaluated with fairness and rigor of the researchers, will emerge as completely baseless and meaningless. Because following the hadith and obeying the Prophet BUH are two essentially same things, which is repeatedly mentioned in the Holy Quran. In this article we have critically examined the concept ’’Denial of hadith due to its compilation’’.